State analysis of tax systems and tax accounting of individual EU countries - Islamli, Jeyhun (Public Policy and Accounting, 2024)
The study shows that the tax systems of the European Union countries have common features and significant differences due to the economic, social and historical characteristics of each state. They are aimed at ensuring sustainable economic development, financing public services and supporting social welfare. Tax accounting and administration in EU countries demonstrates a variety of approaches to the formation of the tax base, rates and collection mechanisms. Some countries, such as Finland, use a progressive taxation scale for individuals, while others, such as Estonia, prefer proportional rates. Differences in corporate tax levels also reflect different models of business incentives and investment attraction. It is important to note the trend towards harmonisation of tax rules within the EU to ensure transparency and competitiveness of economies. At the same time, double taxation avoidance mechanisms and tax incentives are tools that facilitate the integration of EU countries into the global economy. Despite their complexity and differences, the EU tax systems remain factors of balanced economic growth, support for innovation, environmental initiatives and social protection. Understanding their features and current changes is important for businesses operating within the European Union. Another important aspect is the impact of digitalisation and automation of tax administration processes, which significantly increases the efficiency of tax collection and reduces opportunities for evasion. The growing focus on sustainable development is prompting EU countries to introduce environmental taxes, which are becoming a key tool in the fight against climate change and contribute to the formation of a green economy.